Research progress on application of five-element music therapy in perioperative patients (五行音乐疗法在围手术期患者中的应用进展) - QIU Jingyi (邱静怡); RONG Mingmei (戎明梅) (Journal of International Translational Medicine Limited, 2024)
Interventions targeting the psychological status and related symptoms of perioperative patients can accelerate recovery. Five-element music therapy, as a non-pharmacological intervention method, has gained increasing attention in perioperative patient care due to its drug-free nature, lack of side effects, strong feasibility, and significant therapeutic effects. This article provides an overview of the principles of five-element music therapy, as well as intervention strategies and application effects during the perioperative period, aiming to provide references and guidance for further clinical practice. (围手术期患者的心理状态与预后密切相关。作为一种非药物干预方法, 五行音乐疗法应用于围手术期患者的心理护理中有积极作用。本文阐述五行音乐疗法的原理, 综述其在围手术期患者中的应用, 探讨后续的研究方向, 为临床推广五行音乐疗法提供参考依据。)